Simbol-Simbol pada Novel Charlotte’s Web Karya E.B White - Gistari Gistari (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This research aims to analyze the symbols in the novel Charlotte's Web. The author choses this topic because wanted to understand the symbols contained in the novel and study them.the writing uses the semiotic method by Roland Barthes, and the kualitatif analysis datathis study shows symbols in the novel are depicted in words, actions and characters. A very important symbol in the novel is the spider's web. The main character is closely related to this symbol.the writer hopes this study can help students to understand symbols at charlotte's web